2000
DOI: 10.1067/mtc.2000.108902
|View full text |Cite
|
Sign up to set email alerts
|

Better preservation of endothelial function and decreased activation of the fetal renin-angiotensin pathway with the use of pulsatile flow during experimental fetal bypass

Abstract: Improved placental and peripheral perfusion during fetal pulsatile-flow bypass may be mediated by preservation of fetal/maternal endothelial nitric oxide biosynthetic mechanisms and/or decreased activation of the fetal renin-angiotensin pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
(33 reference statements)
0
32
0
6
Order By: Relevance
“…Pulsatil akımın kullanıldığı diğer deneysel çalışmalarda; fetal pulsatil akım ile periferik vasküler dirençte azalma ve uteroplasental üniteden nitrik oksit gibi vazodilatör faktör-lerin salınımına bağlı olarak maternal kalp debisinde artış sağlanmış (5) . Endotel fonksiyonlarının daha iyi korunduğu, fetal renin-anjiotensin aktivasyonunda azalma olduğu ve laktat seviyelerinin nonpulsatil akı-ma göre daha stabil olduğu da gösterilmiştir (6) . KPB sırasında; maternal sirkülasyon, asid-baz dengesi ve perfüzyon basıncı stabil olsa bile anestezik ilaçlara özellikle opioidlere bağlı fetal kalp hızı değişiklikleri görülebilir.…”
Section: Discussionunclassified
“…Pulsatil akımın kullanıldığı diğer deneysel çalışmalarda; fetal pulsatil akım ile periferik vasküler dirençte azalma ve uteroplasental üniteden nitrik oksit gibi vazodilatör faktör-lerin salınımına bağlı olarak maternal kalp debisinde artış sağlanmış (5) . Endotel fonksiyonlarının daha iyi korunduğu, fetal renin-anjiotensin aktivasyonunda azalma olduğu ve laktat seviyelerinin nonpulsatil akı-ma göre daha stabil olduğu da gösterilmiştir (6) . KPB sırasında; maternal sirkülasyon, asid-baz dengesi ve perfüzyon basıncı stabil olsa bile anestezik ilaçlara özellikle opioidlere bağlı fetal kalp hızı değişiklikleri görülebilir.…”
Section: Discussionunclassified
“…In previous CPB ovine fetal models, the placenta served as the sole oxygenator, resulting in unstable oxygenation and severe placental damage occurring (24,25). It was observed that inhibiting stress and protecting vascular endothelial function of the placenta following CPB prevented an increase in the vascular resistance of the placenta that would otherwise lead to impairment of placental function, irreversible acidosis and subsequent fetal death (24).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that inhibiting stress and protecting vascular endothelial function of the placenta following CPB prevented an increase in the vascular resistance of the placenta that would otherwise lead to impairment of placental function, irreversible acidosis and subsequent fetal death (24). During CPB, the following typically influence the extent of placental damage: i) Re-distribution of fetal blood flow, ii) placental vascular endothelial dysfunction, iii) humoral factors, iv) perfusion patterns, v) pre-perfusion solution, and vi) low temperatures (25). Synergistic effects of these factors may cause progressive hypoxia, hypercapnia, acidosis and mortality of the fetuses (20,26).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow and microvascular blood flow both decrease, while the expression of inflammatory mediators in blood and vascular cells increases when pulsatile flow is replaced with nonpulsatile flow. [22][23][24] To circumvent this, some groups have added aortic counterpulsation attempting to reproduce pulsatile flow in the operating room, albeit with limited success. [22][23][24] (5) Alveolar blood flow is compromised.…”
Section: Physiologic Consequences Of Cardiopulmonary Bypassmentioning
confidence: 99%
“…[22][23][24] To circumvent this, some groups have added aortic counterpulsation attempting to reproduce pulsatile flow in the operating room, albeit with limited success. [22][23][24] (5) Alveolar blood flow is compromised. A common perception is that the alveoli are supplied by bronchial arterial blood, the flow of which is not interrupted by cardiopulmonary bypass.…”
Section: Physiologic Consequences Of Cardiopulmonary Bypassmentioning
confidence: 99%